The Influence of Brand Super-Recovery Effort, Online Brand Community Engagement, and Empathy on Repurchase Intention Among Generation Z Who Actively Shop for Local Fashion Online on the Shopee Platform through Consumer Forgiveness as a Mediation Variable - Mutiara Dias Faradisa; Ratna Listiana Dewanti (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study aimed to analyze the influence of brand super-recovery effort, online brand community engagement, and empathy on repurchase intention among Generation Z consumers who actively shop for local fashion online through the Shopee platform, with consumer forgiveness as a mediating variable. The sampling in this research was purposive sampling technique, with a sample size of 153 respondents. The research employs quantitative data, with primary data collected through an online questionnaire that was tested for validity and reliability. The analysis tool used in this study was Structural Equation Modeling-Partial Least Squares (SEM-PLS). Hypothesis testing was conducted through path analysis. The result of the study indicated that brand super-recovery effort had a positive and significant influence on consumer forgiveness, online brand community engagement had a positive and significant influence on consumer forgiveness, empathy had a positive and significant influence on consumer forgiveness, brand super-recovery effort had a positive and significant influence on repurchase intention, online brand community engagement had a positive and significant influence on repurchase intention, empathy had a positive and significant influence on repurchase intention, consumer forgiveness had a positive and significant influence on repurchase intention, consumer forgiveness mediated the relationship between brand super-recovery effort and repurchase intention, consumer forgiveness mediated the relationship between online brand community engagement and repurchase intention, consumer forgiveness mediated the relationship between empathy and repurchase intention.